2019
DOI: 10.1111/dewb.12231
|View full text |Cite
|
Sign up to set email alerts
|

How do Chinese universities address research integrity and misconduct? A review of university documents

Abstract: Background: Scientific researchers are expected to follow the professional norms in their own domain. With a growing number of scientific publications retracted and research misconduct cases revealed in recent years, Chinese biomedical research integrity is questioned. As institutions educating and training future researchers, universities and the guidance they provide are important for the research quality and integrity of the country. Therefore, through a review of the guidance and policy documents on resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Reconsideration period 1 15 working days (1) national policies. Inappropriate authorship, ghostwriting, multiple contribution, repetitive publication and published in different languages were specified in detail in a few universities, consistent with other study (Yi et al, 2019). Abuses, such as abuse of academic reputation, abuse of academic power, disclosure of academic secrets, and misuse of research resources, are not readily identifiable in many universities.…”
Section: Research Misconduct Acceptance and Investigation Mechanismmentioning
confidence: 54%
See 2 more Smart Citations
“…Reconsideration period 1 15 working days (1) national policies. Inappropriate authorship, ghostwriting, multiple contribution, repetitive publication and published in different languages were specified in detail in a few universities, consistent with other study (Yi et al, 2019). Abuses, such as abuse of academic reputation, abuse of academic power, disclosure of academic secrets, and misuse of research resources, are not readily identifiable in many universities.…”
Section: Research Misconduct Acceptance and Investigation Mechanismmentioning
confidence: 54%
“…Most colleges and universities in China have promulgated policies to clarify the content and requirements of RI. They have set up a management or advisory office to carry out the specific management work of RI and to formulate norms and systems (Yi et al, 2019). Therefore, in this study, we took the top 50 universities in China, as ranked by the 2021 Best Chinese Universities Ranking (Ranking, 2021), as the research sample.…”
Section: Sampled University Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ensures that other areas of the institution are cognizant of the breach and assists in facilitating a uniform approach to implementing academic integrity policy across the academic community. A recent investigation into the handling of academic integrity infractions in China (Yi et al, 2019) revealed that Chinese institutions are starting to take the phenomenon seriously. The study found that punishments included academic sanctions, such as the retraction of awards or cancellation of funding, institution-imposed sanctions that could include demotions or dismissals and even referral to the Communist Party for consideration of further punitive actions.…”
Section: Academic Misconductmentioning
confidence: 99%
“…Although reliable dissemination of research is critical to the advancement of knowledge, the past 3 to 4 decades have witnessed growing concerns over the integrity of the scientific and scholarly record. In response, governments [ 1 4 ] and research institutions across the world [ 5 , 6 ] have developed guidance for avoiding ethically questionable practices and, especially, the more serious forms of research misconduct.…”
Section: Introductionmentioning
confidence: 99%